Complementary and Alternative Medicine on Youtube: An Exploratory Study of Content-Creatir Communities - Cano-Orón, Lorena (2023)
The objective of this article is to explore the communities generated on YouTube by content creators on complementary and alternative medicine (CAM). Through graph theory, visual network analysis and a broad overview of the content of selected channels, communities are examined to assess their strength as a community in terms of their degree of connectedness and density. Strong communities are composed of individuals who spread the word about the same topic and viewpoint, acting as one block. Results showed that content creators who promote CAM on YouTube have small and weak communities; in contrast, content creators related to scientific dissemination, who are against CAM, have built strong communities.